2009
DOI: 10.1136/vetrec.165.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and efficacy of teicoplanin against intramammary infections in sheep

Abstract: The pharmacokinetics of teicoplanin were evaluated in 10 healthy sheep. After intravenous injection it showed monophasic behaviour, with a short mean (sd) elimination half-life (5 [0.24] hours). After intramuscular injection its bioavailability was 100 per cent but it was absorbed slowly; its elimination half-life was satisfactorily slow (9.23 [0.74] hours). Its efficacy was evaluated in 26 crossbreed sheep with milk positive to strains of Staphylococcus aureus, coagulase-negative staphylococci and Streptococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In our previous investigation, the therapeutic efficacy of Thymus vulgaris essential oils has been documented in ovine mammary postural dermatitis [34] but currently, there are no studies on the topical use in dog skin infections. Anyway, the topical use of EOs on the skin…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous investigation, the therapeutic efficacy of Thymus vulgaris essential oils has been documented in ovine mammary postural dermatitis [34] but currently, there are no studies on the topical use in dog skin infections. Anyway, the topical use of EOs on the skin…”
Section: Discussionmentioning
confidence: 99%
“…r. l., Milano, Italy) and measuring the diameter of the growth inhibition area, as recommended by CLSI (Clinical and Laboratory Standards Institute 2015) [34]. In particular, in vitro Open Journal of Veterinary Medicine -12.5 µg/ml and greater than 12.5 µg/ml respectively.…”
Section: In Vitro Antimicrobial Activitymentioning
confidence: 99%
“…Specifically, of the 580 original papers on the general topic of mastitis in sheep, only 50 (8.6%) reported work on the treatment of the infection [ 1 ]. Relevant papers described treatment regimes with the administration of antibiotics in clinical cases [ 2 , 3 , 4 ] or in experimental work [ 5 ] on ovine mastitis, whilst other papers focused on supportive treatment, e.g., with non-steroid anti-inflammatory drugs [ 6 ]. Papers on the antibiotic susceptibility of bacterial isolates recovered from cases of mastitis have also been published [ 7 , 8 , 9 ], as this is important for the implementation of the correct treatment regimes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Naccari et al [ 3 ] studied the efficacy of a single injection of tilmicosin (dose rate: 10 mg kg −1 bodyweight) against staphylococcal mastitis and reported a full cure within 7 days after treatment. In a further study, Naccari et al [ 4 ] reported that three injections of teicoplanin (a semi-synthetic glycopeptide antibiotic) at the dose rate of 6 mg kg −1 of bodyweight resulted in a complete clinical and bacteriological cure of staphylococcal mastitis within up to 30 days after administration. Thereafter, the efficacy of enrofloxacin against staphylococcal mastitis (caused by Staphylococcus aureus or coagulase-negative staphylococci) was evaluated by Attili et al [ 5 ], who reported that administration at the dose rate of 6 mg kg − 1 of bodyweight, twice daily for three days, showed 82% efficacy based on the results of bacteriological examinations.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to the article ‘Pharmacokinetics and efficacy of teicoplanin against intramammary infections in sheep’ by Naccari and others (2009). WHO has classified antimicrobials into classes of importance, according to defined criteria (FAO/OIE/WHO 2008, Collignon and others 2009).…”
mentioning
confidence: 99%